2011
DOI: 10.4088/jcp.09m05853blu
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoproteins Improve After Successful Pharmacologic Antidepressant Treatment

Abstract: German Clinical Trial Registry Identifier: DRKS00000008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 0 publications
1
35
3
Order By: Relevance
“…This is consistent with earlier research indicating an association among low HDL, hypertriglyceridemia and clinical depression (Hummel et al, 2011;Scharnholz et al, 2014;van Reedt Dortland et al, 2010). The lack of an association between depression and obesity accords with a previous study using adolescent and elderly populations (Kuo et al, 2011), but other results are equivocal (Byers et al, 2012;Luppino et al, 2010;Scharnholz et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with earlier research indicating an association among low HDL, hypertriglyceridemia and clinical depression (Hummel et al, 2011;Scharnholz et al, 2014;van Reedt Dortland et al, 2010). The lack of an association between depression and obesity accords with a previous study using adolescent and elderly populations (Kuo et al, 2011), but other results are equivocal (Byers et al, 2012;Luppino et al, 2010;Scharnholz et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Although other preclinical studies have not revealed any effect of venlafaxine on blood sugar level [9], our results present a significant decrease of blood glucose, despite of high triglyceride levels. This unexpected metabolic changes lead us to one possible explanation for the effect of venlafaxine on lipid and glucose homeostasis which means a presumptuous association between venlafaxine and peroxisome proliferator-activate receptor gamma (PPAR ) nuclear receptor.…”
Section: Discussioncontrasting
confidence: 36%
“…Cholesterol was quantified by commercial enzymatic methods using a random-access analyser (Modular, Roche Diagnostics, Mannheim, Germany) as described by Hummel et al (2011). For quantification of HDL and LDL cholesterol, lipoprotein fractions were separated by ultracentrifugation over a time period of 18 h at 100.000 g in a 50.4 Ti rotor with a Beckman L-60 ultracentrifuge (Beckman Coulter, Munich, Germany).…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Effective antidepressant pharmacotherapy modulates some of the dyslipidemic patterns observed in depressive patients, especially total cholesterol, HDL and LDL cholesterol (Hummel et al, 2011;Maes et al, 1997;Rabe-Jablonska and Poprawska, 2000). This may be a primary effect of the pharmacotherapy itself or may follow the amelioration of depressive symptoms.…”
Section: Introductionmentioning
confidence: 96%